Exploratory study on the relationship between urinary sodium/potassium ratio, salt intake, and the antihypertensive effect of esaxerenone: the ENaK Study - Katsuya, Tomohiro; Inobe, Yoshito; Uchiyama, Kazuaki; Nishikawa, Tetsuo; Hirano, Kunio; Kato, Mitsutoshi; Fukui, Toshiki; Hatta, Tsuguru; Iwasaki, Arata; Ishii, Hajime; Sugiura, Toshiyuki; Taguchi, Takashi; et al. (Hypertension Research, 2024)
Excessive salt intake is one of the causes of hypertension, and reducing salt intake is important for managing the risk of hypertension and subsequent cardiovascular events. Esaxerenone, a mineralocorticoid receptor blocker, has the potential to exert an antihypertensive effect in hypertensive patients with excessive salt intake, but evidence is still lacking, especially in clinical settings. We aimed to determine if baseline sodium/potassium ratio and baseline estimated 24-h urinary sodium excretion can predict the antihypertensive effect of esaxerenone in patients with essential hypertension inadequately controlled with an angiotensin receptor blocker (ARB) or a calcium channel blocker (CCB). This was an exploratory, open-label, interventional study with a 4-week observation period and a 12-week treatment period. Esaxerenone was orally administered once daily in accordance with the Japanese package insert. In total, 126 patients met the eligibility criteria and were enrolled (ARB subcohort, 67; CCB subcohort, 59); all were included in the full analysis set (FAS) and safety analysis. In the FAS, morning home systolic blood pressure (SBP)/diastolic blood pressure (DBP) significantly decreased from baseline to end of treatment (primary efficacy endpoint) (−11.9 ± 10.9/ − 6.4 ± 6.8 mmHg, both p < 0.001); a similar trend was observed in both subcohorts. Significant reductions were also shown in bedtime home and office SBP/DBP (all p < 0.001). Each BP change was consistent regardless of the urinary sodium/potassium ratio or estimated 24-h urinary sodium excretion at baseline. The urinary albumin-creatinine ratio (UACR) and N-terminal pro-brain natriuretic peptide (NT-proBNP) significantly decreased from baseline to Week 12 in the total population and both subcohorts. No new safety concerns were raised. Esaxerenone significantly decreased morning home, bedtime home, and office BP; UACR; and NT-proBNP in this patient population, regardless of concomitant ARB or CCB use. The antihypertensive effect of esaxerenone was independent of the urinary sodium/potassium ratio and estimated 24-h urinary sodium excretion at baseline.